Validation of FAT4CP © first aid module and assessment tool: Evaluating module acceptance and the Knowledge, Attitude And Confidence (KAC) on first aid response among childcare providers - Juliana N.; Teng N.I.M.F.; Kamal N.I.A.M.; Johari S.M.; Amin N.A.; Abu I.F.; Azmani S. (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by Scopus